Effects of exercise training on left ventricular function and exercise capacity in patients with coronary artery disease and varying degrees of left ventricular dysfunction - Digenio, Andres G (MRC/UCT RU for Exercise and Sport Medicine, 2018)
The medical profession has increased its acceptance of the benefits of exercise training for patients with uncomplicated coronary artery disease. Access to more modem technology and better management of this condition has led to an increase in the number of patients surviving acute coronary episodes . Some of these patients may have developed chronic asymptomatic left ventricular dysfunction and/or residual myocardial ischaemia, and could become potential candidates for cardiac rehabilitation if exercise training could induce physiological benefits without further deteriorating their condition. Over the last 10 years, several patients at moderate to high risk of future cardiovascular events because of the presence of left ventricular dysfunction and/or myocardial ischaemia have been accepted for cardiac rehabilitation at the Johannesburg Cardiac Rehabilitation Center. The purpose of the study was to evaluate the effects of exercise training on left ventricular function and exercise capacity in patients with coronary artery disease and varying degrees of left ventricular dysfunction and/or myocardial ischaemia attending the Johannesburg Cardiac Rehabilitation Center.